Medicines Reuse - Donyai, Parastou (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint examines the concept of medicines reuse, the idea that unused medication returned by one patient can be re-dispensed for use by another. Ten papers written by over 20 authors examine a range of issues related to medicines reuse including the circular economy of the pharmaceutical supply chain; the prevalence of unused medicines or medication waste within patients' homes; people's views about the causes of medication waste and the potential for medicines reuse; what might influence people to reuse medicines in the future; how sensing technologies might facilitate medicines reuse; and the effect of including sensing technologies on people's willingness to consider medicines reuse.